Comparative Evaluation of Tooth Displacement Between Clear Aligners and Fixed Appliance with And Without Mini-Implant Placement During Intrusion of Maxillary Anterior Teeth- A 3-Dimensional Finite Element Analysis - Banerjee, Shounak; Kumar Balani, Rajesh; Kallury, Amitabh; Jain, Shashank; Shukla, Shambhavi (Journal of Neonatal Surgery, 2025)
Aim: The present study is a FEM study assessing the amount of displacement of tooth during intrusion of maxillary anterior teeth for correction of gummy smile using clear aligners and conventional brackets with and without the use of mini-implants. Materials and methods: Cone Beam Computerized Tomography (CBCT) scan which were obtained from DENTSPLY Sirona Ortophos SL 80kv 9500 cone beam 3D Extra oral imaging system with are construction volume of 50x37 mm and are constructed matrix voxel of 0.2x0.2x0.2 um. The equipment had CMOS (Complementary Metal Oxide Semiconductor) sensor technology. The field of view was 11 x 10 mm, exposure parameters for the patients varied from 70k V8mA with a scan time of 14 seconds. All the teeth were assessed by the 3D volume tricimage and 1 mm tomographic sections in sagittal, axial and coronal planes. Result: The greatest displacement of tooth during intrusion of maxillary anterior teeth was seen clear aligners with e-chain and mini-screws and the least displacement of tooth was seen along with conventional brackets with burstone intrusion arch. Conclusion: Gummy smile correction using clear aligners and e-chain is the best treatment modality among all four models in planning maxillary anterior intrusion.